2016
DOI: 10.3319/tao.2016.07.30.01
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Climate Change Impact on Gilgel Abbay and Gumara Watershed Hydrology, the Upper Blue Nile Basin, Ethiopia

Abstract: Climate change and variability have significant influences on hydrological cycles and the availability of water in the Horn of Africa. Projections of six General Circulation Models (GCMs) in association with high (A2) and low (B1) emission scenarios were adopted in this study from the Special Report on Emission Scenarios (SRES) for the period 2020 -2039 to assess the impacts of climate changes on the Gilgel Abbay and Gumara watershed hydrology, the upper Blue Nile basin, Ethiopia. The GCMs selected were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
9
12
1
Order By: Relevance
“…These results are in agreement with results from previous studies in the Lake Tana basin (Gebre and Ludwig 2015;Ayele et al 2016;Nigatu et al 2016;Melke and Abegaz 2017), though variations exist in the magnitude of change, which could be due to differences in GCM models, emission scenarios, and downscaling methods used between studies. However, this result contradicted with the study by Setegn et al (2011) in the Lake Tana basin who reported decreasing trends in future rainfall.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are in agreement with results from previous studies in the Lake Tana basin (Gebre and Ludwig 2015;Ayele et al 2016;Nigatu et al 2016;Melke and Abegaz 2017), though variations exist in the magnitude of change, which could be due to differences in GCM models, emission scenarios, and downscaling methods used between studies. However, this result contradicted with the study by Setegn et al (2011) in the Lake Tana basin who reported decreasing trends in future rainfall.…”
Section: Discussionsupporting
confidence: 92%
“…These results are comparable with the previous studies (Dile et al 2013;Nigatu et al 2016;Liersch et al 2018;Mekonnen and Disse 2018) in the Upper Blue Nile basin. Besides, the results agree with the study by Ayele et al (2016) in Gilgel Abay and Gumara watersheds. They reported that projected (2020-2039) temperature in the A2/B2 scenarios will increase by 1.2/1.1°C and 0.8/0.7°C in Gilgel Abay and Gumara watershed, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations